Progesterone (P4) ameliorates cigarette smoke-induced chronic obstructive pulmonary disease (COPD) - Bin Xie; Qiong Chen; Ziyu Dai; Chen Jiang; Xi Chen (BMC, 2024)
Abstract Background Chronic obstructive pulmonary disease (COPD) is a chronic inflammatory lung disease associated with high morbidity and mortality worldwide. Oxidative injury and mitochondrial dysfunction in the airway epithelium are major events in COPD progression. Methods and results The therapeutic effects of Progesterone (P4) were investigated in vivo and in vitro in this study. In vivo, in a cigarette smoke (CS) exposure-induced COPD mouse model, P4 treatment significantly ameliorated CS exposure-induced physiological and pathological characteristics, including inflammatory cell infiltration and oxidative injury, in a dose-dependent manner. The c-MYC/SIRT1/PGC-1α pathway is involved in the protective function of P4 against CS-induced COPD. In vitro, P4 co-treatment significantly ameliorated H2O2-induced oxidative injury and mitochondrial dysfunctions by promoting cell proliferation, increasing mitochondrial membrane potential, decreasing ROS levels and apoptosis, and increasing ATP content. Moreover, P4 co-treatment partially attenuated H2O2-caused inhibition in Nrf1, Tfam, Mfn1, PGR-B, c-MYC, SIRT1, and PGC-1α levels. In BEAS-2B and ASM cells, the c-MYC/SIRT1 axis regulated P4's protective effects against H2O2-induced oxidative injury and mitochondrial dysfunctions. Conclusion P4 activates the c-MYC/SIRT1 axis, ameliorating CS-induced COPD and protecting both airway epithelial cells and smooth muscle cells against H2O2-induced oxidative damage. PGC-1α and downstream mitochondrial signaling pathways might be involved.